Des traces d’artisanat dans les monastères comtois du haut Moyen Âge - Sébastien Bully; Aurélia Bully; Inès Pactat (contribution) (Bulletin du Centre d’Études Médiévales d’Auxerre, 2015)
Despite the substantial amount of archaeological research carried out on Early Medieval monasteries in Franche-Comté over recent years, the reality of artisanal production within these establishments remains difficult to clarify, given the lack of any substantial material remains. However, thanks to some exceptional finds, which emerged from excavations at Saint-Claude, Luxeuil, Baume and Jussamoutier de Besançon, it is possible for us to nevertheless begin to examine artisanal activity within the monastic precinct, while considering a number of underlying questions: who was involved in this activity, what did their work entail, and to whom was their production targeted?